2011
DOI: 10.1007/s10735-011-9326-6
|View full text |Cite
|
Sign up to set email alerts
|

The possible role of L-carnitine on the skeletal muscle of ovariectomized rats

Abstract: Low muscle strength is observed during the peri-and postmenopausal periods, when the secretion of ovarian hormones is drastically reduced. It is also a predictive of adverse health events as well as incident mobility limitation and disability. The objective of the present study is to study the biochemical and the histological changes in the skeletal muscle of premature menopause-induced rats and the possible protective role of L-carnitine. Ovariectomized (OVX) rats were gavaged with L-carnitine (100 mg/kg) dai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…It significantly decreased triglycerides, ACP, and ALP, and improved bone microstructure by decreasing bone turnover (Hooshmand et al, 2008). In OVX rats, L-carnitine decreased muscle damage suggesting a potential protective effect against postmenopausal myopathy (Moustafa and Boshra, 2011). The current evidence does not support CoQ10 supplementation in statins' myopathy (Schaars and Stalenhoef, 2008).…”
Section: Fig 3 Effects Of Treatments (For Eight Weeks) On Serum Levementioning
confidence: 64%
See 2 more Smart Citations
“…It significantly decreased triglycerides, ACP, and ALP, and improved bone microstructure by decreasing bone turnover (Hooshmand et al, 2008). In OVX rats, L-carnitine decreased muscle damage suggesting a potential protective effect against postmenopausal myopathy (Moustafa and Boshra, 2011). The current evidence does not support CoQ10 supplementation in statins' myopathy (Schaars and Stalenhoef, 2008).…”
Section: Fig 3 Effects Of Treatments (For Eight Weeks) On Serum Levementioning
confidence: 64%
“…The OVX rats were randomly divided into five groups (n=8) treated daily for eight weeks by oral gavage as follows: OVX-untreated (saline), OVX+ E2 (17β-estradiol, 0.1 mg/kg (Huber et al, 2007)), OVX+AT (atorvastatin, 50 mg/kg (Uyar et al, 2009;Chang et al, 2011)), OVX+AT+LC (atorvastatin+ L-carnitine, 100 mg/kg (Moustafa and Boshra, 2011)), and OVX+AT+CQ (atorvastatin+CoQ10, 20 mg/kg (Chirapapaisan et al, 2012)). At the end of treatment, BMD and BMC were measured.…”
Section: Ovariectomy and Experimental Designmentioning
confidence: 99%
See 1 more Smart Citation
“…The results indicated that the addition of L-carnitine in the diet of the cats does not affect the serum levels of estrogen, progesterone and testosterone after ovariohysterectomy. Mustafa et al conducted the study on ovariectomized rats (26). The rats were gavaged with 100 mg/kg L-carnitine for 60 days.…”
Section: Discussionmentioning
confidence: 99%
“…In a menopausal setting, twelve weeks of endurance exercise have been demonstrated to provide some benefits in increasing lipid oxidation, besides improving other cardiorespiratory parameters [135, 136]. Carnitine, which is essential to long-chain fatty acid beta-oxidation, has been shown to recover some of skeletal muscle function and inhibit alterations in ovariectomized rats [137]. Nevertheless, to the best of our knowledge, no work on the impact of carnitine on lipid profile and oxidation in the menopausal heart has been provided.…”
Section: Cardiac Mitochondrial Fatty Acid Beta-oxidation In Healthmentioning
confidence: 99%